Prevalence of voice handicap among nurses in intensive care units due to occupational noise during pandemic - Ziwei Song; Pyoung-Jik Lee; HeeJung Jung (Frontiers Media S.A., 2023)
BackgroundHealthcare workers have been identified as being at risk of occupational voice disorders. Among them, nurses working in intensive care units (ICUs) are particularly vulnerable due to the risk factors that are associated with their exposure to high levels of noise. Thus, this study aimed to determine the prevalence of voice disorders among ICU nurses.MethodsA questionnaire was administered to 100 ICU nurses from four hospitals in China. The questionnaire assessed vocal-related symptoms, perceived voice handicap, frequently heard noise sources, and the quality of communications.ResultsResults indicate that the most frequently reported voice symptoms were 'voice tiredness' and 'voiceless'. Nurses working more than 50 h per week experienced voice symptoms more frequently than nurses working for 40-50 h per week. The median value of the perceived voice handicap score (VHI-30) was 23, indicating mild voice handicap, while 24% of the nurses reported severe voice handicap. Longer working hours and working at patient wards were significantly associated with higher VHI-30 scores. The nurses also reported that the quality of verbal communication with patients and colleagues and voice problems worsened during the COVID-19 pandemic.ConclusionMore than 20% of nurses reported severe voice handicap, however, voice handicap among ICU nurses did not appear universally to all nurses. Further research is necessary to identify the risk factors associated with voice disorders and the mechanism behind such heterogeneity among ICU nurses.